Long-Term Functional Outcomes of Trauma Patients With Facial Injuries. Issue 8 (November 2021) - McCarty, Justin C.; Herrera-Escobar, Juan P.; Gadkaree, Shekhar K.; El Moheb, Mohamad; Kaafarani, Haytham M.A.; Velmahos, George; Salim, Ali; Nehra, Deepika; Caterson, Edward J.
Abstract : Background: Facial trauma can have long-lasting consequences on an individual's physical, mental, and social well-being. The authors sought to assess the long-term outcomes of patients with facial injuries. Methods: This is a prospective multicenter cohort study of patients with face abbreviated injury scores ≥1 within the Functional Outcomes and Recovery after Trauma Emergencies registry. The Functional Outcomes and Recovery after Trauma Emergencies registry collects patient-reported outcomes data for patients with moderate-severe trauma 6 to 12 months after injury. Outcomes variables included general and trauma-specific quality of life, functional limitations, screening for post-traumatic stress disorder, and postdischarge healthcare utilization. Results: A total of 188 patients with facial trauma were included: 69.1% had an isolated face and/or head injury and 30.9% had a face and/or head injuries as a part of polytrauma injury. After discharge, 11.7% of patients visited the emergency room, and 13.3% were re-admitted to the hospital. Additionally, 36% of patients suffered from functional limitations and 17% of patients developed post-traumatic stress disorder. A total of 34.3% patients reported that their injury scars bothered them, and 49.4% reported that their injuries were hard to deal with emotionally. Conclusions: Patients who sustain facial trauma suffer significant long-term health-related quality of life consequences stemming from their injuries. Abstract : Supplemental Digital Content is available in the text